SWICOS (SWISS LONGITUDINAL COHORT STUDY IN RURAL SWITZERLAND): DESCRIPTIVE ANALYSIS OF INITIAL RESULTS. (June 2018) - Muggli, F.; Radovanovic, D.; Schoenenberger, A.W.; Suter, P.M.; Gallino, A.; Parati, G.; Ehret, G.; Berzins, R. Schoenenberger; Resink, T.J.; Erne, P.
Abstract : Objective: Increased longevity necessitates new approaches to reduce the burden of age-related diseases to maintain optimal quality-of-life. This prospective longitudinal study aims to examine the health status and disease risk factors in a Swiss cohort to suggest innovative strategies for healthy aging Design and method: Inhabitants of two villages in Southern Switzerland (Cama and Lostallo) were eligible. Examinations and measurements included medical history, anthropometry, cardiac and vascular health, pulmonary function, physical performance, nutritional, mental and emotional status and biochemical analyses. Between April 9, 2015 and December 31, 2017, 415 patients were included in the study. We performed a first descriptive preliminary analysis on 344 participants Results: Sixty-three participants (19%) were hypertensive and on treatment: prevalence of hypertension increased with the age (among participants < 40 years: 0%; among 40 to 60 years old: 20% for males, 11% for females; 41% among participants > 60 years: 41% for males and females. Similar age-dependent increases were found for diabetes and hyperlipidaemia. Among participants < 40 years, 27% males and 28% females were smoking, whereas only 20% males and 9% females of participants > 60 years were currently smoking. Light physical activity (walking, gardening): among participants < 40 years, 39 minutes per day (males) and 36 minutes per day (females), whereas those > 60 years: 91 minutes per day (males) and 55 minutes per day (females). Excessive body weight is more common among males (75%) than females (30%) in subjects 40 to 60 years of age Conclusions: Smoking and physical inactivity are more common among young participants. Excessive body weight is very common among males 40 to 60 years of age. The remaining cardiovascular risk factors were increasingly prevalent with increasing age.